2021
DOI: 10.1186/s12872-021-02373-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndrome with non-obstructive coronary arteries (ACS-NOCA) in patients with hypertrophic cardiomyopathy

Abstract: Objectives Our study aimed to determine the prevalence and prognosis of acute coronary syndrome with non-obstructive coronary artery (ACS-NOCA) in patients with hypertrophic cardiomyopathy (HCM). Methods and results We enrolled a total of 200 consecutive patients with HCM over a 139-month period from 2002 to 2013. The study found that 28 patients (14% of overall patients, 51% of patients with ACS) had ACS-NOCA, and 18 patients (9% of overall patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Mechanisms that are unique to HCM include (i) increased left ventricular wall thickness and (ii) increased left ventricular intracavitary pressures due to outflow or mid‐cavitary obstruction 44 . Indeed, acute coronary syndrome without obstructive coronary artery is not an uncommon initial presentation (prevalence 9–14%) in patients with HCM 45 . Macrovascular disease is also common in HCM with a prevalence of up to 53% 46,47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms that are unique to HCM include (i) increased left ventricular wall thickness and (ii) increased left ventricular intracavitary pressures due to outflow or mid‐cavitary obstruction 44 . Indeed, acute coronary syndrome without obstructive coronary artery is not an uncommon initial presentation (prevalence 9–14%) in patients with HCM 45 . Macrovascular disease is also common in HCM with a prevalence of up to 53% 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…44 Indeed, acute coronary syndrome without obstructive coronary artery is not an uncommon initial presentation (prevalence 9-14%) in patients with HCM. 45 Macrovascular disease is also common in HCM with a prevalence of up to 53%. 46,47 Bariatric surgery can theoretically improve control of chronic stable angina and prevent acute coronary syndrome in HCM via addressing risk factors of both microvascular and macrovascular disease (e.g.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Davlat et al ( 23 ) demonstrated the association of left ventricular non-compaction with ACS. Moreover, Puwanant et al ( 24 ) presented a cohort of 200 patients with hypertrophic cardiomyopathy (HCM) suffering a higher prevalence of ACS. Therefore, it is essential to distinguish the onset of ACS as a significant symptom before the dominant phenotype of cardiomyopathies appears.…”
Section: Discussionmentioning
confidence: 99%
“…Частота больных с инфарктом миокарда в анамнезе в нашем исследовании была намного выше, чем в Тайваньском исследовании (15 % и 3 %) [12], а частота больных с инфарктом миокарда без значимых стенозов коронарных артерий была сопоставима с результатами исследования Puwanant S. et al (7,5 % и 9 % соответственно) [13]. По-видимому, помимо атеросклероза коронарных артерий, при ГКМП микрососудистая дисфункция, стеноз интрамуральных коронарных артерий и дисфункция эндотелия могут способствовать развитию ишемии и/или инфаркта миокарда.…”
Section: Discussionunclassified